Microbial Fabrication of Nanomaterial and Its Role in Disintegration of Exopolymeric Matrices of Biofilm - Nag, Moupriya; Lahiri, Dibyajit; Sarkar, Tanmay; Ghosh, Sujay; Dey, Ankita; Edinur, Hisham Atan; Pati, Siddhartha; Ray, Rina Rani (Frontiers in Chemistry, 2021)
Bacterial biofilms are responsible for the development of various chronic wound related and implant mediated infections and confer protection to the pathogenic bacteria against antimicrobial drugs and host immune responses. Hence biofilm mediated chronic infections have created tremendous burden upon health care systems worldwide. The development of biofilm upon the surface of medical implants has resulted in the failure of various implant-based surgeries and therapies. Although different conventional chemical and physical agents are used as antimicrobials, they fail to kill the sessile forms of bacterial pathogens due to the resistance exerted by the exopolysaccharide (EPS) matrices of the biofilm. One of the major techniques in addressing such problem is to directly check the biofilm formation by the use of novel antibiofilm materials, local drug delivery and device associated surface modifications but the success of these techniques are still limited. The immense expansion in the field of nanoscience and nanotechnology has resulted in the development of novel nanomaterials as biocidal agents that can be either easily integrated within biomaterials to prevent the colonization of microbial cells or directly approach the pathogen overcoming the biofilm matrix. The antibiofilm efficacies of these nanomaterials are accomplished by the generation of oxidative stresses and through alterations of the genetic expressions. Microorganism assisted synthesis of nanomaterials paved the path of bringing success in such therapeutic approaches are found to be more acceptable for their “greener”’ approach. Metallic nano particles functionalized with microbial enzyme, silver-platinum nanohybrids (AgPtNHs), bacterial nanowires, superparamagnetic Iron Oxide (Fe3O4), nanoparticles synthesised by both magnetotactic and non-magnetotactic bacteria showed are some of the examples of such agents to be used to attack the EPS.